2019
DOI: 10.1111/anae.14510
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative optimisation of the surgical patient with diagnosed and undiagnosed diabetes: a practical review

Abstract: Peri-operative hyperglycaemia, whether the cause is known diabetes, undiagnosed diabetes or stress hyperglycaemia, is a risk factor for harm, increased length of stay and death. There is increasing evidence that peri-operative hyperglycaemia is a modifiable risk factor, and many of the interventions required to improve the outcome of surgery must be instituted before the actual surgical admission. These interventions depend on communication and collaboration within the multidisciplinary team along each stage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 52 publications
(66 reference statements)
0
34
0
10
Order By: Relevance
“…Patients are rarely informed in a timely manner about the benefits of lifestyle changes [6] and most patients participating in this study believed it was too late to change lifestyle weeks before surgery. If patients optimise their own health before surgery by exercising, improving nutritional status, or discontinuing smoking, alcohol and other substances they can reduce complications [6,7,30,31]. A major study on orthopaedic patients found that ceasing smoking six to eight weeks before surgery could reduce overall complications from 56 to 18% [32].…”
Section: Discussionmentioning
confidence: 99%
“…Patients are rarely informed in a timely manner about the benefits of lifestyle changes [6] and most patients participating in this study believed it was too late to change lifestyle weeks before surgery. If patients optimise their own health before surgery by exercising, improving nutritional status, or discontinuing smoking, alcohol and other substances they can reduce complications [6,7,30,31]. A major study on orthopaedic patients found that ceasing smoking six to eight weeks before surgery could reduce overall complications from 56 to 18% [32].…”
Section: Discussionmentioning
confidence: 99%
“…26 Only a few well-designed controlled studies are available in the orthopedic setting, 27 and the implementation of effective procedures in frail hyperglycemic patients by dedicated teams requires special attention. 28…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for neuropsychological complications including obesity, diabetes, and dyslipidemia have been reported [2]. The number of people with diabetes mellitus (DM) worldwide has increased to about 425 million [3] and over 90% of those people have type 2 diabetes mellitus (T2DM) caused by diet and lifestyle [4]. In the early postoperative period, cognitive outcome is worse in DM patients than in non-diabetic patients [5], and transient advanced mental impairment occurs more frequently in DM patients after aortic surgery [6].…”
Section: Introductionmentioning
confidence: 99%